Development and validation of an autophagy-related long non-coding RNA prognostic signature for cervical squamous cell carcinoma and endocervical adenocarcinoma - Zhou, Shuguang; Zhang, Weiyu; Cao, Wujun; Jin, Qinqin; Jiang, Xiya; Jiang, Xiaomin; Yang, Yinting; Yao, Hui; Chen, Guo; Gao, Wei; Zhu, Yuting; Qi, Jian; et al. (Frontiers in Oncology, 2022)
Background: In this study, we aimed at investigating the signature of the autophagy-related lncRNAs (ARLs) and performing integrated analysis with immune infiltration in cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC). Methods and Results: The UCSC Xena and HADb database provided the corresponding data. The ARLs were selected via constructing a co-expression network of autophagy-related genes (ARGs) and lncRNAs. Univariate Cox regression analysis combined with LASSO regression and multivariate Cox regression were utilized to screen lncRNAs. The ARLs risk signature was established by Cox regression and tested if it was an independent element bound up with patients prognosis. We used the xCell algorithm and ssGSEA to clarify the pertinence between immune infiltration and the expression of ARLs. Finally, we predicted sensitivity of drug treatment as well as the immune response. Results indicated that the three prognostic ARLs (SMURF2P1, MIR9 - 3HG and AC005332.4) possessed significant diversity and constituted the ARLs signature. The risk score was an individual element (HR= 2.82, 95 % CI= 1.87 - 4.30; p < 0.001). Immune infiltration analysis revealed significant increases in central memory CD8+ T-cells, Endothelial cells, CD8+ naive T-cells and Preadipocytes in the high-risk group (p < 0.05). There were ten therapeutic agents that varied significantly in their estimated half-maximal inhibitory concentrations in two groups. According to the experimental validation, we found that SMURF2P1 belongs to the co-stimulatory genes,and might assume greater importance in the development of cervical adenocarcinoma. MIR9 - 3HG and AC005332.4 belonged to the tumor suppressor genes and they maybe play a more positive role in the cervical squamous cell carcinoma. Conclusions: This research explored and validated a novel signature of the ARLs, which can apply to forecast the prognosis of patients with CESC and was closely associated with immune infiltration.